Evaluation of sarcopenia in female patients with fibromyalgia syndrome: an ultrasonographic approach - Karvanli, Salih; Karakose, Serdar; Ugurlu, Hatice (Frontiers in Medicine, 2025)
ObjectivesThe aim of this study is to evaluate sarcopenia in female patients with Fibromyalgia Syndrome (FMS), according to diagnostic algorithms, in terms of total and regional muscle mass measurements.MethodsThe study included 60 female patients diagnosed with FMS (mean [M] = 47.78 years, Standard deviation [SD] = 4.72 years) and 30 healthy women (M = 49.8 years, SD = 4.8 years). The ages and anthropometric measurements were noted, and participants evaluated using the Widespread Pain Index, Symptom Severity Scale, Visual Analog Scale, Fatigue Severity Scale, Beck Depression Inventory, International Physical Activity Questionnaire, and the Fibromyalgia Impact Questionnaire.ResultsThe hand grip strength and gait speed values of the patient group were found to be lower than those of the control group, and the chair stand test value higher than that of the control group. There was a statistically significant difference between the groups (p < 0.01). Two individuals in the patient group were classified as having sarcopenia according to the ISarcoPRM algorithm. No statistically significant difference was found between the patient group and the control group in terms of anterior thigh muscle thickness, sonographic thigh adjustment ratio, and skeletal muscle mass index (p = 0.897, p = 0.829, p = 0.706).ConclusionThe female patients with FMS were dynapenic, which means a loss of muscle function without a loss of muscle mass.